Aclareo de frutos de pitaya (Stenocereus griseus) en la región mixteca baja oaxaqueña - Sánchez Trujano, Jacqueline (Universidad Autónoma Metropolitana, 2006)
The Pitaya is a traditional resource of great economic importance in the Mixteca Baja Oaxaqueña. The pitayas is inside the native fruits of our country that have generated an increase in the economic entrance in the farmer in some areas and they have increased the consumer's acceptance. However there are not enough studies on their reproductive biology. The investigation was carried out in the area of the Mixteca Baja Oaxaqueña, in 2004, in a pitayos vegetable garden Stenocereus griseus Haworth applying manual fruit thining of immature fruits with the purpose of observing the effect in function to the following parameters; polar and equatorial diameter, I weigh, brix, pH, acidity titulable, besides the previous one was also evaluated the dry matter. The treatments were applied independently by individual and simultaneously. The fruits that remained were marked and followed until their maturation. We present data of the floral biology. They were carried out experiments of fruit thining, having controls (branches without fruit thining) and branches with fruit thining of the 20 and 33% of their fruits. When being harvested them were quantified: polar, equatorial diameter, I weigh and index of roundness; stability of the pulp; total soluble solids and pH in the juice; I weigh of the shell; I weigh of the seeds. The variables evaluated without effect of the treatments (covariables) they were: the longitude of the arm and the rib number. Although the results don't show significant differences, a tendency was presented to the increase of the content of sugar in the treatments with more fruit thining. We cannot discard the possibility of changes in these variables in serial years, for that which investigations are required to longer term.; La Pitaya es un recurso tradicional de gran importancia económica en la Mixteca baja Oaxaqueña. Las pitayas se encuentran dentro de las frutas nativas de nuestro país que han generado un aumento en el ingreso económico en el campesino en algunas zonas y han aumentado la aceptación del consumidor. Sin embargo no hay estudios suficientes sobre su biología reproductiva. La investigación se realizó en la zona de la mixteca baja oaxaqueña, en 2004, en una huerta de pitayos Stenocereus griseus Haworth aplicando aclareo manual de frutos inmaduros con la finalidad de observar el efecto en función a los siguientes parámetros; diámetro polar y ecuatorial, peso, brix, pH, acidez titulable, además de los anterior se evaluó también la materia seca. Los tratamientos fueron aplicados independientemente por individuo y simultáneamente. Los frutos que permanecieron fueron marcados y seguidos hasta su maduración. Presentamos datos de la biología floral. Se realizaron experimentos de aclareo de frutos, contando con controles (ramas sin raleo) y ramas con raleo del 20 y 33% de sus frutos. Al ser cosechados se cuantificaron: diámetro polar, ecuatorial, peso e índice de redondez; firmeza de la pulpa; sólidos solubles totales y pH en el jugo; peso de la cáscara; peso de las semillas. Los variables evaluadas sin efecto de los tratamientos (covariables) fueron: la longitud del brazo y el número de costilla. A pesar de que los resultados no muestran diferencias significativas, se presentó una tendencia al aumento del contenido de azúcar en los tratamientos con mayor raleo. No podemos descartar la posibilidad de cambios en estas variables en años consecutivos, para lo cual se requieren investigaciones a más largo plazo.